(untitled) - Sors, Laszlo (New York, 1989)
This book is based on the authors' many years of experience in the practice and teaching of mould design. It contains the solutions to the most interesting problems they have encountered during their work. Books on this subject are not very numerous as designers are often reluctant to publish the results of their experiences. This work, however, offers a broad survey of constructional designs which have proved feasible in practice. Through studying these examples designers may find useful ideas for solving other problems.
Keywords: Plastics; Molds,Design and construction